2006
DOI: 10.1177/0011128705281749
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment for Criminal Thinking

Abstract: Risk assessments generally rely on actuarial measures of criminal history. However, these static measures do not address changes in risk as a result of intervention. To this end, this study examines the basic psychometric properties of the TCU Criminal Thinking Scales (TCU CTS), a brief (self-rating) instrument developed to assess cognitive functioning expected to be related to criminal conduct. Findings demonstrate that these scales have good psychometric properties and can serve as a short but reliable self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
156
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 119 publications
(167 citation statements)
references
References 34 publications
8
156
0
3
Order By: Relevance
“…It contains 16 sub-scales grouped into four dimensions (motivation/need, psychological functioning, social functioning and treatment engagement), for which norms have been established in almost 10,000 clients in the US. The CTS [20] is a 37-item questionnaire with established psychometric properties, consisting of six scales, each assessing an aspect of criminal thinking: Entitlement, Justification, Personal irresponsibility, Power orientation, Cold heartedness and Criminal rationalisation. It has been validated by research within the US criminal justice system and scores have been shown to be responsive to treatment [20] .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…It contains 16 sub-scales grouped into four dimensions (motivation/need, psychological functioning, social functioning and treatment engagement), for which norms have been established in almost 10,000 clients in the US. The CTS [20] is a 37-item questionnaire with established psychometric properties, consisting of six scales, each assessing an aspect of criminal thinking: Entitlement, Justification, Personal irresponsibility, Power orientation, Cold heartedness and Criminal rationalisation. It has been validated by research within the US criminal justice system and scores have been shown to be responsive to treatment [20] .…”
Section: Methodsmentioning
confidence: 99%
“…The CTS [20] is a 37-item questionnaire with established psychometric properties, consisting of six scales, each assessing an aspect of criminal thinking: Entitlement, Justification, Personal irresponsibility, Power orientation, Cold heartedness and Criminal rationalisation. It has been validated by research within the US criminal justice system and scores have been shown to be responsive to treatment [20] . Both assessments were amended for use with a UK population and the changes ratified with the authors of the original instruments.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations